2017
DOI: 10.5312/wjo.v8.i2.115
|View full text |Cite
|
Sign up to set email alerts
|

Failed medial patellofemoral ligament reconstruction: Causes and surgical strategies

Abstract: Patellar instability is a common clinical problem encountered by orthopedic surgeons specializing in the knee. For patients with chronic lateral patellar instability, the standard surgical approach is to stabilize the patella through a medial patellofemoral ligament (MPFL) reconstruction. Foreseeably, an increasing number of revision surgeries of the reconstructed MPFL will be seen in upcoming years. In this paper, the causes of failed MPFL reconstruction are analyzed: (1) incorrect surgical indication or inap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 48 publications
0
35
1
1
Order By: Relevance
“… 11 Mistakes in the femoral attachment point have resulted in increased patellofemoral contact pressure, increased rates of MPFL reconstruction failure, and loss of graft isometry. 3 , 9 In the present study, it was observed that certain patients may have had more errors with the 2D method (female patients with trochlear dysplasia), but this was not a significant finding. The clinical relevance of this finding lies in the fact that lateral patellar instability is more frequent in female patients with severe trochlear dysplasia.…”
Section: Discussioncontrasting
confidence: 62%
“… 11 Mistakes in the femoral attachment point have resulted in increased patellofemoral contact pressure, increased rates of MPFL reconstruction failure, and loss of graft isometry. 3 , 9 In the present study, it was observed that certain patients may have had more errors with the 2D method (female patients with trochlear dysplasia), but this was not a significant finding. The clinical relevance of this finding lies in the fact that lateral patellar instability is more frequent in female patients with severe trochlear dysplasia.…”
Section: Discussioncontrasting
confidence: 62%
“…[3][4][5]13,37,43,58,68 One of the primary causes of these complications is technical surgical errors, of which femoral tunnel malpositioning has been found to be one of the most common. 10,43,51,52,68 Knowledge about the native anatomy and understanding its function are paramount in ligament reconstruction. The anatomy of the MPFL has been heavily debated, and recent publications have shown variability of its femoral attachment.…”
mentioning
confidence: 99%
“…Feller et al[ 36 ] tension the graft with one quadrant of lateral translation in knee extension, then the knee is flexed to 20° for permanent fixation. Other authors prefer techniques with the use of 30° of knee flexion for graft fixation[ 8 , 26 , 28 ] and some prefer a position between 60° and 90° of flexion because this might allow a more precise settling of the patella within the deeper, more inferior parts of the trochlear groove[ 37 ]. Therefore, finding the most appropriate technique for graft fixation seems quite confusing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our technique to simply test and balance the tension during knee motion before permanent fixation might be a feasible and satisfying solution. Considering that 30° of knee flexion seems to be recommended most frequently in the literature[ 8 , 26 , 28 ], we begin with a temporary graft fixation at 30° of flexion. Only after testing and balancing the tension is the graft permanently fastened[ 14 ].…”
Section: Discussionmentioning
confidence: 99%